Examining cultural planning in Vienna - Astrid Krisch (PlaNext, 2019)
Culture and planning have often been connected through issues of culture-led urban development and regeneration or cultural and creative industries. However, cultural provision as a form of social infrastructure has rarely been used to understand the institutionalization of culture within planning practices. I claim that how culture is institutionalized through discursive interactions between different agents reveals the importance of culture for planning practices. I exemplify this notion by analysing the discursive institutionalization of culture within strategic planning in Vienna. The results point to a diametral position of the underlying ideas of culture within planning in Vienna: 1) planning for culture, where culture plays an important role for the social functioning of the city, and 2) planning through culture by using culture as a selling point for the city. The paper analyses cultural planning practices in Vienna since the 2000s, thereby contributing to detailed knowledge on the institutionalization of culture and path-dependent developments of culture within urban planning practices. The paper illustrates the use of culture as a form of social infrastructure for rethinking strategic cultural planning in Vienna.